LINGUISTIC STUDY OF SELECT TURKISH PLACE NAMES THROUGH THE KALEIDOSCOPE OF GREEK VOCABULARY - Sankar Bıswas (International Journal of Language and Translation Studies, 2021)
This present study zeroes in on the elucidation about the often bypassed but tacit linguistic ligature between two languages namely Turkish amp; Greek spoken in two maritime border sharing countries namely Turkey and Greece. The study revisits the glorious past by alluding to historical contexts to justify the indispensability of the Juggernaut Grecian linguistic Influence on Turkish. The study underscores the fact that it is a naturally acceptable phenomenon that one language will influence the other through mutual vocabulary acclimatization due to geographical proximity and vice versa To do justice and to lend weight to the very defense of the influence on the first language of the second mostly in the domain of placenames, the study resorts to the broaching of a curated list of Turkish words vis-à-vis their Greek counterparts through the usage of search engines namely lexilogos.com and etymononline.com . It embarks upon the odyssey of elucidating the behind-the-scenes operationalization of linguistic techniques such as Grin’s Law and Vowel Mutation Law accentuating the very process of derivation of select Turkish place names from Grecian Parallels by attempting a kaleidoscopic analysis. The study ultimately logically drives in home a conclusion that Turkish capitulation to Greek for the appellation of select place names in the Turkish mainland was both an inevitable phenomenon and is a linguistically acceptable no-surprise experientiality.